THE ROLE OF THE GOVERNMENT’S INTERNAL CONTROL SYSTEM, E-PROCUREMENT, APIP CAPABILITIES, AND ORGANISATIONAL CULTURE IN FRAUD PREVENTION IN GOVERNMENT PROCUREMENT OF GOODS AND SERVICES - Wijang Ardi Rahmadi; Ayatulloh Michael Musyaffi; Adam Zakaria (Adisam Publisher, 2026)
This study aims to analyse the influence of the effectiveness of the Government Internal Control System (SPIP), the implementation of e-procurement, the capabilities of the Government Internal Audit Agency (APIP), and organisational culture on the prevention of fraud in the procurement of government goods and services. The background to this study is based on the prevalence of irregularities in public sector procurement processes, despite the implementation of various control mechanisms and digitalisation. This study employs a quantitative approach with an explanatory research design. Primary data were collected via a survey using a questionnaire. The sample comprised 202 respondents, who were Internal Government Oversight Officers (APIP) at Inspectorates within 19 Ministries/Agencies in the Polhukam PMK sector, selected using proportionate stratified random sampling. Hypothesis testing and data analysis were conducted using Structural Equation Modelling – Partial Least Squares (SEM-PLS) with the aid of SmartPLS software. The research results demonstrate that the effectiveness of the government’s internal control system, e-procurement, APIP capabilities, and organisational culture have a positive and significant influence on fraud prevention. In particular, organisational culture was found to be the variable with the most dominant influence in determining the success of fraud prevention within government agencies. The findings of this study provide a theoretical and practical contribution, demonstrating that fraud prevention cannot rely solely on strengthening formal systems and updating technology, but is instead largely determined by the internalisation of integrity values and the exemplary conduct of leadership within the agency.